2022
DOI: 10.1111/inr.12796
|View full text |Cite
|
Sign up to set email alerts
|

The effect of talent management on the job satisfaction and organizational commitment of nurses

Abstract: AimTo determine the effect of talent management on job satisfaction and organizational commitment of nurses and the mediating role of job satisfaction.BackgroundTalent management plays a critical role in attracting, developing, and retaining nurses and is effective in the formation of job satisfaction and organizational commitment.MethodsThis correlational study sample consisted of 482 volunteering nurses who were selected through a convenience sampling method. Data were collected using an information form, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…(2023) [23] , they illustrated that approximately half of the participants had fair degree of knowledge about TM. This was against with Taie, (2015) [38] ; El Dahshan et al, (2018) [16] ; and Al-Maashani et al, (2019) [4] they mentioned that the high number of the participates had unsatisfactory level of knowledge about TM.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(2023) [23] , they illustrated that approximately half of the participants had fair degree of knowledge about TM. This was against with Taie, (2015) [38] ; El Dahshan et al, (2018) [16] ; and Al-Maashani et al, (2019) [4] they mentioned that the high number of the participates had unsatisfactory level of knowledge about TM.…”
Section: Discussionmentioning
confidence: 97%
“…Many organizations see retention as a strategic opportunity to keep their workforce competitive. The challenge of retaining talent in the face of competition from worldwide markets makes it an organizational priority and a critical differentiator in human capital management (Gül et al, 2023) [23] . Talent retention intends to implement policies that will encourage nurses to work for the hospital for the duration as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Also, other researchers indicated that remuneration-based motivation, training and support in professional development were considered to be key issues of satisfaction of healthcare workers ( Anlesinya et al, 2019 ). A study conducted in India found that all talent management practices in healthcare organizations can increase nurses’ job satisfaction and organizational commitment ( Gül et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%